Electrical asymmetry effects in magnetized capacitively coupled plasmas in argon. (16th May 2017) - Yang, Shali; Zhang, Ya; Wang, Hong-Yu; Wang, Shuai; Jiang, Wei
Abstract: Geometrically symmetric and electrically asymmetric discharges operating at 13.56 MHz and 27.12 MHz with variable phase angle between the harmonics are simulated by a one-dimensional implicit particle-in-cell/Monte Carlo collision model in argon at a pressure of 30 mTorr. The amplitude of each of the harmonics is chosen to be 150 V. The magnetic fields, with strengths of 10 G and 100 G, are parallel to the electrodes and homogeneous throughout the entire electrode gap in a direction perpendicular to the electrodes. It is found that, with a weaker magnetic field at 10 G, the plasma density is nearly doubled and the self-bias is almost unaffected. However, with a stronger magnetic field at 100 G, the plasma density is significantly increased and nearly independent of the phase angle, but at the cost of decreasing the self-bias, which results in a smaller adjustable range of ion bombardment energy. In general, we have demonstrated that an external magnetic field will expand the operational parameter spaces and thus may promote some related applications in coupled plasma sources with electrical asymmetry effects.